Partial replacement of soybean meal by meat and bone meal in diets for Nile tilapia juveniles - Abimorad, Eduardo Gianini; Castellani, Daniela; Gonçalves, Giovani Sampaio; Romera, Daiane Mompean; Garcia, Fabiana; Nascimento, Thiago Matias Torres do (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effects of the partial replacement of soybean meal by meat and bone meal in diets for juvenile Nile tilapia on digestibility, health, performance, and feeding cost. The experiment was carried out for 14 weeks, with 400 juveniles (4.9±0.6 g) distributed randomly into 16 tanks. The fish were fed with four diets containing 0, 15, 30, and 45% replacement of protein from soybean meal by protein from meat and bone meal. Performance parameters, digestibility, hematology, and feeding cost were evaluated. The best results for weight gain and apparent feed conversion were observed with 40 and 32% replacement, respectively. The lowest feeding cost was obtained with 30 and 45%. There was a linear decrease in the apparent digestibility coefficients of protein with increasing levels of meat and bone meal. Fish fed diets containing up to 24% replacement show increase of hemoglobin concentration. The diet with 32% replacement of protein from soybean meal by protein from meat and bone meal promotes better feeding conversion for Nile tilapia.